Serious Games: Mechanisms and Effects - Ritterfeld, Ute; Cody, Michael J.; Vorderer, Peter (Routledge, 2009)
Serious Games provides a thorough exploration of the claim that playing games can provide learning that is deep, sustained and transferable to the real world. "Serious games" is defined herein as any form of interactive computer-based game software for one or multiple players to be used on any platform and that has been developed to provide more than entertainment to players. With this volume, the editors address the gap in exisiting scholarship on gaming, providing an academic overview on the mechanisms and effects of serious games. Contributors investigate the psychological mechanisms that take place not only during gaming, but also in game selection, persistent play, and gaming impact. The work in this collection focuses on the desirable outcomes of digital game play. The editors distinguish between three possible effects -- learning, development, and change -- covering a broad range of serious games’ potential impact. Contributions from internationally recognized scholars focus on five objectives: Define the area of serious games Elaborate on the underlying theories that explain suggested psychological mechanisms elicited through serious game play, addressing cognitive, affective and social processes Summarize the empirical evidence on the effectiveness of serious games, Introduce innovative research methods as a response to methodological challenges imposed through interactive media Discuss the possibilities and limitations of selected applications for educational purposes. Anchored primarily in social science research, the reader will be introduced to approaches that focus on the gaming process and the users’ experiences. Additional perspectives will be provided in the concluding chapters, written from non-social science approaches by experts in academic game design and representatives of the gaming industry. The editors acknowledge the necessity for a broader interdisciplinary study of the phenomena and work to overcome the methodological divide in games research to look ahead to a more integrated and interdisciplinary study of digital games. This timely and singular volume will appeal to scholars, researchers, and graduate students working in media entertainment and game studies in the areas of education, media, communication, and psychology. Ute Ritterfeld , Professor for Media Psychology, received her education in the Health Sciences (Academy of Rehabilitation in Heidelberg) and in Psychology (University of Heidelberg), completed her Ph.D. in Psychology (Technical University in Berlin), and habilitated at the University of Magdeburg, Germany. She was Assistant Professor at the University of Magdeburg, Adjunct Professor at the Universities of Berlin (Humboldt) and Hannover, and Associate Professor at the University of Southern California (USC) in Los Angeles, Annenberg School for Communication. At USC, Ritterfeld directed an interdisciplinary research team devoted to the studies of digital games and hosted the inaugural academic conference on serious games. In 2007, Ritterfeld joined the faculty of Psychology and Education at the VU University Amsterdam and co-founded the Center for Advanced Media Research Amsterdam (CAMeRA@VU) where she serves as director of interdisciplinary research. Ritterfeld co-edits the Journal of Media Psychology published by Hogrefe. Michael Cody is Professor of Communication at the University of Southern California Annenberg School for Communication. He earned his Ph.D. in Communication at Michigan State University in 1978, where he focused on research methods and face to face social influence processes. He has authored or edited books in persuasion, interpersonal communication and entertainment education. He is the editor of the Journal of Communication (2009-2012). Peter Vorderer (Ph.D., Technical University of Berlin), is Scientific Director of the Center for Advanced Media Research Amsterdam (CAMeRA) and head of the Department of Communication Science, VU University Amsterdam, The Netherlands. He specializes in media use and media effects research with a special focus on media entertainment and digital games. Together with Dolf Zillmann and Jennings Bryant, he has edited three well-recognized volumes on media entertainment and video games.